The Development of Computer Technology and its Impact on Digital Society - Deitje Sofie Pongoh; Clayton Berhitu; Christoper Tamba; Melky Timbuleng; Jerry Samuel; Rifqi Chairullah (Jurnal Syntax Admiration, 2025)
The rapid evolution of computer technology, from its inception in the 19th century to the current era of globalization and digitalization, has profoundly impacted modern society. This research examines the effects of technological advancements on various aspects of life, including the economy, social interactions, education, and security, while addressing the challenges posed by the digital divide and data privacy concerns. The study aims to explore the transformative role of technology in shaping the digital society, identify key problems faced in this era, and propose strategies to mitigate negative impacts. Using a qualitative approach, the research analyzes data gathered from online sources and environmental observations to compare and synthesize findings. The results highlight significant benefits, such as enhanced communication, increased productivity, and improved access to information, alongside drawbacks like job displacement, mental health issues, and cybersecurity threats. The study underscores the urgency of digital literacy and adaptive skills to navigate technological changes effectively. Implications suggest the need for inclusive policies to bridge the digital divide and robust frameworks to safeguard privacy, ensuring equitable access and sustainable growth in the digital age